Mudanças no mundo do trabalho, educação e reprodução social dos industriários no Ceará. - Maia, Maryland Bessa Pereira (2010)
The present doctoral thesis falls within the line of Economy Politics Sociability and Education in the Graduate Program in Brazilian Education at the Federal University of Ceará while integrating the production of the Work Studies Laboratory (LABOR) The object of our study is the schooling of the industrial working class propitioned by the industrial bourgeoisie of Ceará from an analysis of the Worker’s Education Program developed by the Industrial Social Services linked to the Federation of State Industries The research is characterized as qualitative Case Study using procedures such as documental analyses bibliographic and observer/ participant It is a reference point—theoretical—methodological elaborated by Louis Althusser in that it refers to the concept of reproduction of relationships of capitalist production and the ideological school mechanism that offered us subsidiaries to understand the relationships and the reproduction originating from a project in classist industrial bourgeoise The rich experience of studies and research left us with an inheritance for the doctoral candidate interested in investigation of other possible lines of research beginning with Marxist perspectives of the Praxis as the formative principle of the industrial working class The guise of considerations faced with the results generated by this research we advocate that basic schooling as a way to foster worker habits and the particular form of the Education of Work provided by the Industrial Social Service in Ceará has relevant influence in the reproduction of relationships of class of these workers Along with this, noteworthy is that in the historical context of the poor unskilled worker the Program takes a form of upward social mobility with the possibility of only having access to consumer goods that capital produces However the need arises to think about a school Program that has as its guiding path educational action focused on human emancipation and not only the reproduction of capitalist production relationships